CYCLIC SYSTEM FOR TRAINING SPECIALISTS OF ECONOMIC SECURITY OF ENTERPRISES AND ORGANIZATIONS - M. N. Vlasenko; L. M. Kunbutayev; S. V. Potekhetsky (Вестник университета)
It has been proved that the introduction of a cyclic system of professional training of specialists in economic security of enterprises and organizations contributes to increasing the efficiency of their functioning, competitiveness, financial and economic stability in the conditions of market uncertainty. It has been established that the introduction of cyclic methods of the systematic development of professional competencies of specialists of economic security must be implemented based on the results of the preliminary assessment of the internal and external environment of the enterprise, the main threats and risks posed by them. The main stages of organizing and conducting cyclical professional training have been developed, the factors contributing to the adaptation of the training system to the specifics of the enterprise have been identified, the content, essence, procedure for conducting educational and methodological activities have been described. The main restrictions and priorities in the organization and conduct of educational and methodological activities aimed at ensuring the required level of economic security of production facilities have been ascertained. The list of current and prospective tasks that need to be solved during the implementation of training activities has been defined.